The Effect of Curing Temperature on the Mechanical Characteristics of Paving Blocks with Fly Ash and Coconut Fiber Mixture for Road Pavements - Isradi, Muhammad; Nashir, Muhammad Farras; Abdila, Syafiadi Rizki; Sumarno, Agung; Prasetyo, Agus Mudo; Budiman, Johan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The increasing demand for environmentally friendly construction materials has encouraged the use of industrial and organic waste, such as fly ash and coconut fiber, as alternative additives in paving block production. This study aims to evaluate the effects of using fly ash as a partial cement replacement and coconut fiber as an additive on the mechanical strength and environmental aspects of paving blocks. The research method is experimental, based on SNI 03-0691-1996 and ASTM C109/C109M-21 standards. The mix variations consisted of 0%, 10%, 15%, and 20% fly ash, with an addition of 2% coconut fiber, using two curing methods: room temperature and water immersion. The compressive strength test results at 28 days showed that room temperature curing produced values of 11.07 MPa, 11.58 MPa, 12.85 MPa, and 12.06 MPa, respectively. Meanwhile, water immersion curing yielded 14.40 MPa, 14.89 MPa, 16.13 MPa, and 15.69 MPa. The highest flexural strength, 4.25 MPa, was achieved with a mixture of 10% fly ash and 2% coconut fiber cured by water immersion. The use of fly ash and coconut fiber not only enhances the mechanical strength of paving blocks but also contributes to reducing industrial and agricultural waste. This combination has proven effective in improving material performance while supporting sustainable development as an eco-friendly solution